The CDC PNU-1 criteria for diagnosis of ventilator-associated pneumonia - Hapsari Widya Ningtiar; Dwi Putri Lestari; Neurinda Permata Kusumastuti; Arina Setyaningtyas; Retno Asih Setyoningrum; Ira Dharmawati; Abdul Latief Azis (Paediatrica Indonesiana, 2019)
Background Ventilator-associated pneumonia (VAP) is one of the most common nosocomial infections in the pediatric intensive care unit (PICU), with mortality rates of up to 50%. Post-mortem pulmonary examination is considered to be the gold standard for diagnosis of VAP, but is impossible for routine application. The sensitivity and specificity of Clinical Pulmonary Infection Score (CPIS) are considered to be similar to the those of the gold standard, but the Centers for Disease Control and Prevention PNU-1 (CDC PNU-1) is simpler and not invasive, compared to the CPIS. Objective To evaluate the level of agreement between CDC PNU-1 and CPIS criteria in diagnosing VAP. Methods This cross-sectional study was conducted in the PICU at Dr. Soetomo Hospital, Surabaya from June to October 2018. Subjects were children aged 1 month–18 years who had been intubated for more than 48 hours. The VAP diagnoses were made by CDC PNU-1 and CPIS criteria. The level of agreement between the two methods was evaluated by Cohen's Kappa test using SPSS Statistics Base 21.0 software. Results hirty-six subjects were evaluated using CDC PNU-1 and CPIS criteria. Subjects' mean age was 3.5 (SD 4.7) years. Amongst 19 patients with VAP, 14 were diagnosed by CPIS criteria and 17 were diagnosed by CDC PNU-1 criteria. The level of agreement between the CDC PNU-1 and CPIS criteria was good (Kappa 0.61; 95%CI 0.31 to 0.83). The CDC PNU-1 had sensitivity 0.85, specificity 0.77, positive predictive value (PPV) 0.70, and negative predictive value (NPV) 0.89. Conclusion The CDC PNU-1 criteria has a good level of agreement with CPIS criteria in diagnosing VAP.